(untitled) (Medico Legal Update, 2021)
Introduction: Many literatures reported that poor aeration in the middle ear due to Eustachian tube dysfunction is an important factor that plays a role in causing acute and chronic otitis media. Objective: To assess Eustachian tube function (ETF) and to confirm Eustachian tube condition during surgery on chronic suppurative otitis media (CSOM) patients. Method: This study employed a prospective design, in which participants were examined for ETF before and after surgery. The examination used Toynbee’s procedure with impedance audiometry. The examination results were analysed using Pearson’s product-moment test with p < 0.05. Results: The average patient’s age was 36.27 ± 5.98 years, with an age range of 12 to 67 years. Most participants had no cholesteatoma (59.89%), perforation (50.00%), and experienced conductive hearing loss (54.54%). There was no significant difference between ETF and Eustachian tube during surgery (p = 0.439). Conclusion: This study reported that most CSOM patient had total impaired ETF with open Eustachian tube.